Arabidopsis DELLA Protein Degradation Is Controlled by a Type-One Protein Phosphatase, TOPP4 - Qin, Qianqian (Public Library of Science, 2014)
Gibberellins (GAs) are a class of important phytohormones regulating a variety of physiological processes during normal plant growth and development. One of the major events during GA-mediated growth is the degradation of DELLA proteins, key negative regulators of GA signaling pathway. The stability of DELLA proteins is thought to be controlled by protein phosphorylation and dephosphorylation. Up to date, no phosphatase involved in this process has been identified. We have identified a dwarfed dominant-negative Arabidopsis mutant, named topp4-1. Reduced expression of TOPP4 using an artificial microRNA strategy also resulted in a dwarfed phenotype. Genetic and biochemical analyses indicated that TOPP4 regulates GA signal transduction mainly via promoting DELLA protein degradation. The severely dwarfed topp4-1 phenotypes were partially rescued by the DELLA deficient mutants rga-t2 and gai-t6, suggesting that the DELLA proteins RGA and GAI are required for the biological function of TOPP4. Both RGA and GAI were greatly accumulated in topp4-1 but significantly decreased in 35S-TOPP4 transgenic plants compared to wild-type plants. Further analyses demonstrated that TOPP4 is able to directly bind and dephosphorylate RGA and GAI, confirming that the TOPP4-controlled phosphorylation status of DELLAs is associated with their stability. These studies provide direct evidence for a crucial role of protein dephosphorylation mediated by TOPP4 in the GA signaling pathway.